Perspektif Peran Perempuan dalam Film Demi Nama Baik Kampus Analisis Wacana Kritis Model Sara Mills - Dita Isninadia; Achmad Yuhdi (International Forum of Researchers and Lecturers, 2023)
This study examines the perspective of the role of women in the film